Understanding and monitoring the consequences of human impacts on intraspecific variation. (22nd November 2016) - Mimura, Makiko; Yahara, Tetsukazu; Faith, Daniel P.; Vázquez‐Domínguez, Ella; Colautti, Robert I.; Araki, Hitoshi; Javadi, Firouzeh; Núñez‐Farfán, Juan; Mori, Akira S.; Zhou, Shiliang; Hollingsworth, Peter M.; Neaves, Linda E.; et al.
Abstract: Intraspecific variation is a major component of biodiversity, yet it has received relatively little attention from governmental and nongovernmental organizations, especially with regard to conservation plans and the management of wild species. This omission is ill‐advised because phenotypic and genetic variations within and among populations can have dramatic effects on ecological and evolutionary processes, including responses to environmental change, the maintenance of species diversity, and ecological stability and resilience. At the same time, environmental changes associated with many human activities, such as land use and climate change, have dramatic and often negative impacts on intraspecific variation. We argue for the need for local, regional, and global programs to monitor intraspecific genetic variation. We suggest that such monitoring should include two main strategies: (i) intensive monitoring of multiple types of genetic variation in selected species and (ii) broad‐brush modeling for representative species for predicting changes in variation as a function of changes in population size and range extent. Overall, we call for collaborative efforts to initiate the urgently needed monitoring of intraspecific variation.